2010
DOI: 10.1080/14427591.2010.9686688
|View full text |Cite
|
Sign up to set email alerts
|

The interconnected meanings of occupation: The call, being‐with, possibilities

Abstract: While a range of literature has explored the meaning of occupation, the lived experience of occupation has been relatively neglected. In this hermeneutic phenomenological study 12 New Zealand adults who had experienced a disruption to their occupations were interviewed, on the assumption that disruption reveals things that are usually overlooked. The data were analysed by identifying key themes and engaging in a hermeneutic process informed by the philosophies of Heidegger and Gadamer. The findings suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 26 publications
3
56
0
7
Order By: Relevance
“…It is important that the findings support the notion that specific occupational forms and contexts can call for a shift in attunement for individuals (Reed, Hocking, & Smythe, 2010). For example, one participant found that playing his guitar could completely absorb him and allowed him to transcend his immediate situation, even when he was hearing voices.…”
Section: Discussionmentioning
confidence: 68%
“…It is important that the findings support the notion that specific occupational forms and contexts can call for a shift in attunement for individuals (Reed, Hocking, & Smythe, 2010). For example, one participant found that playing his guitar could completely absorb him and allowed him to transcend his immediate situation, even when he was hearing voices.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, engagement in creative and productive occupations can reinforce participants' self-identity and self-esteem (Reed et al 2010, Kielhofner 2002, as seems to have been the case in this project.…”
Section: Music Emotion and Identitymentioning
confidence: 99%
“…For people within residential settings, Carey (2011) found that occupations, particularly those that involved cognition through reminiscence, were valued very highly and that such processes of identity-realisation not only enabled people to feel more linked to their environment but also reinforced their sense of self. Similarly, Reed et al (2010) note that identity is directly influenced by meanings gained from occupational engagement and the influence of the cultural environment.…”
Section: Literature Review Occupation In Later Lifementioning
confidence: 99%
See 1 more Smart Citation
“…According to Robeyns 20 , the valuable options -such as the positive opportunities the women imagined -are what truly count in creating freedom for well-being. Imagining is an endeavor beyond the conventional in order to creatively tap into new possibilities allowing people to be positioned as capable, resilient and pushing boundaries as they journey towards who they are becoming 33 . Through imaginative use of the resources available to them, such as public space, media and relationships, the women were able to accrue and to learn and practice business skills.…”
Section: Capabilities Creativity and Developmentmentioning
confidence: 99%